From homebreakers to jailbreakers: Southall Black Sisters - Gupta, Rahila (Zed Books, 2003)
For over 21 years Southall Black Sisters have spearheaded campaigns in areas as diverse as abused women who kill and changes to the immigration rules. This anthology looks at their work and influence